Lexical Change in Minangkabau Language Found in Andaleh-Sabu - Asraf, Andri Varoqi Latunil; Jufrizal, Jufrizal (English Language and Literature, 2021)
Language is always changed by the time that affected human life and vice versa. This research belonged to the descriptive qualitative research to find out lexical change and their factors that occur in Andaleh-Sabu sub-dialect. Based on data analysis and discussion found 243 words which are almost dead since the young generation does not understand at all with the words, while the old generation still uses this word for daily communications. Afterward, the data were classified into three stages of lexical change, semi-lexical change, lexical shift. There were 84 words as the result of lexical change which are divided into 52 nouns, 12 verbs, 17 adjectives, and 3 adverbs. Furthermore, there were 74 words classified as semi lexical change which were refused by the young generation. This phenomenon occurs due to several factors such as the emergence of the Indonesian language, globalization, migration, intermarriage, and decreasing number of the old generation.